Sharing Information through Delegation and Collaboration - Otto H. Swank; Bauke Visser (Tinbergen Institute, 2004)
This article analyzes under which conditions a manager can motivate a junior worker by verbal communication, and explains why communication is often tied up with organizational choices as job enlargement and collaboration. Our model has two important features. First, the manager has more information about a junior's ability than the junior himself. Second, the junior's effort and ability are complements. We show that the manager has an incentive to exaggerate the junior's ability. We discuss two ways in which the manager can make credible statements about the junior's ability. First, the senior can delegate a task to the junior for which it is important that the junior has a correct perception of his ability. Information is shared through a costless signal. Second, the senior can spend more time on a junior she perceives as able than on a junior she perceives as less able. Information is then shared through a costly signal.
Keywords: C70; D23; D83; 330; Communication; incentives; signalling; overconfidence; delegation; collaboration; Leistungsanreiz; Kooperative Führung; Interne Kommunikation